Sublingual Misoprostol for labour augmentation - Verma, Aruna; Gupta, Abhilasha; Kashyap, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Labour dystocia is associated with a number of adverse maternal and neonatal outcomes. Augmentation of labour is a commonly used intervention in cases of labour dystocia. Misoprostol is an inexpensive and stable prostaglandin E1analogue. Present study was done to see the effectiveness of sublingual misoprostol for labour augmentation and foeto-maternal outcome. Methods: Total 100 labouring women of term gestation were taken and divided in two groups: group A (study group) and group B (control group). In study group 25mcg sublingual misoprostol given 4 hourly till adequate uterine contractions developed, i.e. >3 contractions in 10 minutes, each lasting for 40-45 seconds. A maximum of 200mcg of misoprostol or 8 doses were used and in group B no drug was given for augmentation of labour. Maternal and foetal outcome were observed in both groups. Results: Augmentation to delivery interval was very short in group A in comparison to group B. Maternal and foetal outcome were almost same in both groups. Conclusions: Sublingual misoprostol is a safe and effective drug for augmentation of labour leading to early delivery without any major side effects.